Characteristics of Heavy Metals Adsorption Cu, Pb and Cd Using Synthetics Zeolite Zsm-5 - . Priyadi; . Iskandar; . Suwardi; Rino Rakhmata Mukti (JOURNAL OF TROPICAL SOILS, 2015)
It is generally known that zeolite has potential for heavy metal adsorption. The  objectives of this study were to synthesize and characterize zeolite ZSM-5 and to figure out the adsorption capacity of zeolite ZSM-5 for heavy metals of Cu2+, Pb2+ and Cd2+. Characterization of zeolite ZSM-5 included some variables i.e. crystal structure (XRD), morphology (SEM), specific surface area and total pore volume (N2 physisorption). Adsorption capacity of zeolite ZSM-5 was analysed using a batch system with heavy metals of Cu2+, Pb2+ and Cd2+ in various concentrations (50, 100, 150, 200 and 250 ppm) with contact times 30, 60, 90, 120 and 250 minutes. Adsorption data was calculated by Langmuir and Freundlich isotherm. The results showed that the maximum adsorption capacity of zeolite ZSM-5 against heavy metals of Pb2+, Cu2+, and Cd2+, were 74.07, 69.93 and 60.24 mg g-1, respectively. These indicated that synthetic zeolite ZSM-5 had potential to adsorb heavy metals. The results also suggested that the adsorption capacity was affected by the pore size of zeolite, negative charge of zeolite, diameter of hydrated and electronegative ion.